Efficiency of drip irrigation in amaranth production using the HYDRUS-1D model - Karimov, Akmal; Khalikov, Bakhodir; Isaev, Sabirjan; Sindarov, Obidjon; Khayitov, Kholmurod; Avliyakulov, Mirzoolim; Isashov, Anvarjon; Bulanbayeva, Perizat; Djumanazarova, Altingul; Muhammadov, Yo'ldoshbek; Rajabov, Nurmamat; Murtazayeva, Gulnoza; et al. (Frontiers in Sustainable Food Systems, 2025)
The negative impact of climate change is potentially damaging agroecosystem services that have constrained agricultural production and caused water scarcity in Central Asian countries, particularly in Uzbekistan. This study evaluates the efficiency of full (FDI) and deficit (DDI) drip irrigation regimes for amaranth (Amaranthus spp.) cultivation in the Tashkent region of Uzbekistan using the HYDRUS-1D simulation model. Field experiments were conducted over two growing seasons, accompanied by soil moisture monitoring, root zone analysis, and crop performance measurements while the accuracy of the obtained results was assessed against ground measured data. The results showed that compared to the FDI regime, amaranth under the DDI improved water productivity by 56.5% while exhibiting tolerance to water scarcity. The Pearson correlation analysis revealed a strong relationship between the simulated and observed SWC data for both irrigation regimes (R2 = 0.862 for FDI and R2 = 0.936 for DDI), indicating the model’s predictive reliability. Although FDI produced higher yield (2004 kg/ha) over the two-year period, which was 25% (2 t ha−1) higher than the DDI regime (1,604 kg/ha). However, DDI demonstrated significantly greater water productivity (56.5% higher), attributed to reduced unproductive evaporation and the C4 nature of amaranth. Root system analysis revealed deeper penetration under DDI, suggesting adaptive responses to water stress. The findings of this study suggest that implementing precise irrigation technology in amaranth cultivation combined with the use of the HYDRUS-1D model in the context of inevitable climate change, can ensure the long-term sustainable management of water and land resources in arid regions.